Upaya Diplomasi Perlindungan Berbasis Keamanan Manusia oleh BP3MI Jawa Timur dalam Repatriasi Jenazah Pekerja Migran Indonesia dari Malaysia Tahun 2024 - Rayden Muhammad Hariswan; Moh Fathoni Hakim (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines the legal vacuum in the repatriation of deceased Indonesian Migrant Workers (IMW) from Malaysia in 2024 and the protection diplomacy practices of BP3MI East Java. A juridical-empirical method combines analysis of Law Number 18 of 2017 with a case study of 101 IMW remains repatriations from East Java. The findings identify the absence of a dedicated bilateral Memorandum of Understanding on remains repatriation, normative ambiguity on financing for non-procedural IMWs and an average burden of around twenty million rupiah per case. The study recommends three operational steps: a bilateral MoU with a specific remains clause, revision of Article 27 of Law 18/2017 and the creation of a status-blind emergency fund.